Níveis de cálcio e avaliação óssea e de ovos de avestruzes reprodutoras - Paz, Ibiara Correia de Lima Almeida [UNESP]; Mendes, Ariel Antonio [UNESP]; Balog, A. [UNESP]; Martins, M. R F B [UNESP]; Almeida, I. C L [UNESP]; Fernandes, B. C S [UNESP]; Milbradt, E. L. [UNESP]; Vulcano, Luiz Carlos [UNESP]; Komiyama, C. M. [UNESP]; Cardoso, K. F G [UNESP] (SciELO Espana/Repisalud, 2010)
Analyses of mineral density in tibias and femurs of breeder ostriches had been carried on six couples 5-7 years old. During 8 weeks, 3 couples had been fed with ration of reproduction (T1) and other 3 couples with ration of maintenance (T2). It was possible to verify that the egg production was not affected by the diets, as well as the quality of egg shells. However the quality of the bones was worse for the birds fed of T2.
Calcium levels and evaluation of bone and egg in breeding ostriches
Keywords: Bone quality; Laying; Nutrition; Production; Aves; Struthioniformes